2022
DOI: 10.3390/healthcare10010157
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Management and Impact of Dysmenorrhea on Medical Students’ Lives—A Multicenter Study

Abstract: Introduction: Dysmenorrhea is defined as the presence of painful menstruation, and it affects daily activities in different ways. The aims of this study were to assess the prevalence and management of dysmenorrhea and to determine the impact of dysmenorrhea on the quality of life of medical students. Material and methods: The study conducted was prospective, analytical and observational and was performed between 7 November 2019 and 30 January 2020 in five university centers from Romania. The data was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
(60 reference statements)
8
7
1
Order By: Relevance
“…Regarding menstrual history, the result of the present study declared that less than three quarters of both groups had their menarche at (11-<13). This result is similar to Sima R et al (2022) (24) who proclaimed that the mean age of menarche were 12.39±1.33. In addition, most of the studied students (the study and control groups) had regular menstruation with interval of 28-30 days.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding menstrual history, the result of the present study declared that less than three quarters of both groups had their menarche at (11-<13). This result is similar to Sima R et al (2022) (24) who proclaimed that the mean age of menarche were 12.39±1.33. In addition, most of the studied students (the study and control groups) had regular menstruation with interval of 28-30 days.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, dysmenorrhea was found to be a prevalent gynecological pain amongst medical students with 249 (83%) affected individuals; however, other studies estimated its prevalence in the world at 50 -90% (11,12). This result was in line with other studies that reported the prevalence of dysmenorrhea by 75 -85% (13)(14)(15). In a meta-analysis study, Samani et al reported that prevalence of menstrual disorders in Iran was 73.27% (16).…”
Section: Discussionsupporting
confidence: 89%
“…One major side effect and symptom of dysmenorrhea is usually reported by women in varying capacities is pain [25]. Pain can have a negative impact on overall quality of life and can cause distress or anxiety in women of all ages and ethnicities [26,27,28]. Our present findings suggest that KT is an effective treatment technique to reduce pain in dysmenorrhea in both the short and long term.…”
Section: Discussionsupporting
confidence: 50%